Ultrasound-guided bilateral erector spinae plane block in the management of postoperative analgesia in living liver donors: a randomized, prospective study - Uludağ Yanaral, Tümay; Güngör, Hande; İnce, Ayşe; Çelik, Erkan Cem; Yaprak, Onur; Atalay, Yunus Oktay; Çiftçi, Bahadır; Karaaslan, Pelin (My University, 2024)
BACKGROUND: Living donor hepatectomy is a procedure associated with notable postoperative pain, impacting patient recovery and satisfaction. Addressing this challenge, we aimed to examine the effect of ultrasound-guided bilateral erector spinae plane block (ESPB) in postoperative analgesia management of patients undergoing living donor hepatectomy for liver transplantation. METHODS: Asingle-center prospective, randomized, controlled study was conducted on ASAI-IIpatients aged 18-65 who underwent elective living donor hepatectomy. Participants were randomized into ESPB (N.=20) and control (N.=21) groups. ESPB was performed under ultrasound guidance with 0.25% bupivacaine (20 mLbilaterally) at T7-T9 levels. The control group received no block. Postoperative analgesia included IVacetaminophen, opioids, alongside fentanyl patient-controlled analgesia. Pain intensity was assessed using Numeric Rating Scale (NRS) at various time intervals. Primary outcome was to compare postoperative opioid consumption levels and secondary outcomes were to evaluate postoperative pain scores, requirement of rescue analgesia, and opioid-related side effects. RESULTS: Patients in ESBP group exhibited lower total fentanyl consumption (P=0.023) and lower meperidine use for rescue analgesia (P=0.001) compared to controls. While static pain scores showed no significant difference, Group ESPB reported lower dynamic pain scores in the immediate postoperative period (P=0.047). The incidence of nausea was lower in Group ESPB (6 vs. 17, P=0.002) with no observed complications. CONCLUSIONS: ESPB displayed promise in effectively managing post-living donor hepatectomy pain, resulting in decreased opioid consumption, improved pain relief, and reduced rescue analgesia requirements. This technique holds potential to enhance recovery and patient satisfaction following donor hepatectomy.
Keywords: Acute Pain; Anesthesia; Liver Transplantation; Living Donors; Pain Management; Ultrasonography